UPAYA PENINGKATAN PEMBERDAYAAN KADER DALAM DETEKSI DINI DAN PENCEGAHAN PRE EKLAMPSIA DIWILAYAH PUSKESMAS GUNTUNG MANGGIS KOTA BANJARBARU - Rubiati Hipni; Serilaila Serilaila; Niken Widyastuti Hariati (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Pre-eclampsia is a medical complication in pregnancy more than 20 weeks, the incidence of pre-eclampsia is still quite high in 2017 at Idaman Hospital Banjarbaru where out of 100 pregnant women with preeclampsia the most 36 cases (36%) women gave birth with preeclampsia from the Guntung Manggis Public Health Center area, Prevention efforts against pre-eclampsia can be carried out at the most basic level in the community, namely Posyandu by empowering cadres in early detection and prevention of preeclampsia. This service aims to empower caring cadres to early detection and prevention of pre-eclampsia in the Guntung Manggis Community Health Center, Banjarbaru City. The method is through training and mentoring for cadres using PowerPoint media, videos, flipcharts, and leaflets, the participants consist of 20 delegates from PKM Partners, 10 pregnant women, 1 midwife, and 1 nutritionist at the Guntung Manggis Health Center, evaluated through pre -test and post-test as well as assessing cadre counseling for pregnant women at the posyandu. The results show that there is an increase in improvement from the previous, this indicates that the material presented can be understood by cadres and pregnant women well